The Role of Political Education on The Political Participation of Novice Voters in The 2020 Simultaneous Regional Elections in Barru District - Andi Rosdianti Razak; Jaelan Usman; Rusdin Nawi (Syntax Literate, 2022)
This study aims to answer the main problem discussed, namely the role of political education on the political participation of novice voters in the 2020 Simultaneous Regional Elections in Barru Regency. In addition, to explain the supporting and inhibiting factors of political education in the success of simultaneous regional elections. The method used is qualitative with a phenomenological type, to explain the current status of a group of people, objects and political systems. The data analysis technique used is descriptive qualitative, to comprehensively examine and analyze the role of political education for the younger generation, especially novice voters in participating in the success of the 2020 simultaneous regional elections. The results of this study show that the role of political education for the younger generation, especially novice voters, to participate and be actively involved in the 2020 simultaneous regional elections in Barru Regency is largely determined by various factors, including: the family as an agent of socialization of political education has a very important role. Then a factor that is no less important in motivating novice voters in the 2020 simultaneous regional elections is the social environment. Furthermore, supporting and inhibiting factors in this study include: (1) supporting factors are the presence of political stimuli, personal and social characteristics, and political education; (2) inhibiting factors include busy daily activities, minders, and prohibitions from the family (parents).